Sexual Victimization Among Men: A Qualitative Analysis of the Twitter Hashtag #UsToo - Bogen, Katherine W. (Journal of interpersonal violence, 2022)
The present study sought to characterize use of the hashtag #UsToo on Twitter to disclose or comment on men?s experiences of sexual victimization. A sample of 281 original content, English-language tweets containing the hashtag were collected from Twitter over five consecutive weekdays. Thematic content analysis was conducted by a three-person coding team (full team consensus, achieving 100% agreement). Researchers categorized tweets as either a disclosure of victimization (N = 6) or a response to this hashtag (N = 275). When responding to the hashtag, users commented on the emotional impact of victimization, provided positive responses within the forum (i.e., advocacy, call to action, raising awareness, and prosocial reactions), and also engaged in negative responses within the forum (i.e., distracting attention away from the experiences of victims, egocentric responses which called attention to themselves or others, and otherwise harmful reactions). Despite the popularity of the #MeToo hashtag to disclose personal experiences of violence victimization, Twitter users were unlikely to utilize the hashtag #UsToo to disclose personal experiences of sexual victimization. Results highlight a divergence between online behavior in response to a call for men?s disclosure of sexual victimization using the hashtag #UsToo versus online behavior in response to a call for women?s disclosure of sexual victimization using the hashtag #MeToo.